Analisa Kesehatan dan Keselamatan Kerja (K3) menggunakan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) pada Pembangunan Gerbang Banyuran Tanjung Jati Unit 5 dan 6 di PT. Supraco Indonesia - nur, vaizah; ashari, Faisal (Universitas Bojonegoro, 2023)
This study analyzes Occupational Health and Safety (K3) in the construction of the Banyuran Tanjung Jati Gate Units 5 and 6 at PT. Supraco Indonesia, utilizing the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. HIRARC is a systematic process used to identify hazards, assess risks, and control them to prevent accidents. The research identifies 16 processes, categorizing potential hazards such as material spillage, high-speed driving, and unsafe working conditions like slippery surfaces. Risk assessments show that most identified risks are low, with a few posing moderate risks, such as minor injuries and dehydration. Risk controls implemented include proper safety signage, the use of personal protective equipment (PPE), and ensuring worker competency. These measures aim to minimize workplace accidents and enhance safety for all involved in the construction project.